2018
DOI: 10.7554/elife.33070
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction-induced activation of RNA splicing in the amygdala of microbiome-deficient mice

Abstract: Social behaviour is regulated by activity of host-associated microbiota across multiple species. However, the molecular mechanisms mediating this relationship remain elusive. We therefore determined the dynamic, stimulus-dependent transcriptional regulation of germ-free (GF) and GF mice colonised post weaning (exGF) in the amygdala, a brain region critically involved in regulating social interaction. In GF mice the dynamic response seen in controls was attenuated and replaced by a marked increase in expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 90 publications
5
69
0
Order By: Relevance
“…Moreover, social stimulus evoked an increase in transcripts of genes involved in neuronal activity, which includes induction of several well established immediate early genes such as Fos or Arc, the MAP-K pathway and neurotrophic signalling via Bdnf. Moreover, we find upregulation of complement components, which have lately been established to be necessary for synaptic rearrangements and plasticity upon neuronal activity [6].…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover, social stimulus evoked an increase in transcripts of genes involved in neuronal activity, which includes induction of several well established immediate early genes such as Fos or Arc, the MAP-K pathway and neurotrophic signalling via Bdnf. Moreover, we find upregulation of complement components, which have lately been established to be necessary for synaptic rearrangements and plasticity upon neuronal activity [6].…”
mentioning
confidence: 67%
“…Transcriptomic analysis demonstrated an upregulation of several immediate early response genes such as Fos, Fosb, Egr2 or Nr4a1 in association with increased CREB signalling in GF mice (see [5] for full details). Moreover, when a germ-free mouse is introduced to a social stimulus the normal transcriptional pathway recruitment is absent but instead genes involved in alternative splicing are enriched (see [6] for full details of genes affected)…”
Section: Novel Models Of Drug Relapse and Craving After Voluntary Absmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the strongest evidence for microbial modulation of cognition and behavior in animal models comes from studies of social interactions (Sherwin et al, 2019). Germ-free rodents typically exhibit deficits in both sociability and memory for social stimuli (indexed by preference for a novel social partner; Buffington et al, 2016;Desbonnet et al, 2014;Sgritta et al, 2019;Stilling et al, 2018; but see also Arentsen et al, 2015). Similar effects are observed following antibiotic depletion of the microbiota during development (Degroote et al, 2016;Desbonnet et al, 2015), while administration of certain probiotic species can enhance social behavior in various murine models of autism (Buffington et al, 2016;Hsiao et al, 2013;Sgritta et al, 2019) and inflammation-induced social withdrawal (D'Mello et al, 2015).…”
Section: Behavioral and Cognitive Developmentmentioning
confidence: 99%
“…Early studies showed that germ-free mice (i.e. mice that are raised completely sterile with no internal or external microbiome) have marked deficits in social behaviors and in gene expression profiles in multiple brain regions related to regulation of these behaviors [12][13][14] . Additionally, mice who have had their microbiomes depleted with antibiotics show deficits in social behavior, cognitive flexibility, and multiple other ASD-like behaviors 6,15,16 .…”
Section: Introductionmentioning
confidence: 99%